The IDENTIFIKASI BATUAN BAWAH PERMUKAAN DAERAH PANAS BUMI TAPANULI UTARA MENGGUNAKAN METODE HORIZONTAL TO VERTICAL SPECTRAL RATIO - Iswari, Wita; Juliani, Rita (EINSTEIN (e-Journal), 2026)
The research aims to identify subsurface rocks in the geothermal area of North Tapanuli using the Horizontal to Vertical Spectral Ratio (HVSR) method. The HVSR method analyzes the spectral response of microtremor waves to obtain dominant frequency parameters (f₀) and amplification factors (A₀) that can describe the depth and type of subsurface layers. Data were collected in four locations, namely Partali Toruan village, Parbubu village, Situmeang Hasundutan village, and Simasom Toruan village. The analysis results show that the f₀ values in Partali Toruan Village, Situmeang Hasundutan Village, and Simasom Toruan Village indicate the presence of breccia, andesite, and basalt bedrock in the subsurface and function as cover rock in the geothermal system. Parbubu Village produces f₀ values that indicate an alluvium sedimentary layer. The shear wave velocity (Vs) profiles obtained show a stratigraphic structure typical of volcanic areas, with a significant increase in Vs with depth indicating a transition from medium soil to hard rock.